Urban Residential Segregation in Medium-Sized Cities: A Geographical Analysis of the Castilla y León Region, Spain - Martins Medeiros Robaina, Igor; Carlos Hugo Soria Caceres; Gonzalo Andrés López (Geografares, 2023)
In Spain, medium-sized cities show clearly lower indicators of residential segregation than large urban areas, with a clear contrast between the values for high and low incomes, as well as for the foreign population group. This differentiation is more pronounced in the medium-sized cities of the Castilla y León region, which show particularly moderate levels of residential segregation compared with other cities in the Spanish urban system. However, the gap between socio-economic segregation at the extremes of income is more pronounced. This analysis highlights the complexity of the patterns of socio-spatial differentiation currently present in these cities and paves the way for the study of residential segregation in greater detail by means of infra-municipal scale analysis.